Omics approaches to understanding the efficacy and safety of disease-modifying treatments in multiple sclerosis - Lorefice, Lorena; Pitzalis, Maristella; Murgia, Federica; Fenu, Giuseppe; Atzori, Luigi; Cocco, Eleonora (Frontiers in Genetics, 2023)
From the perspective of precision medicine, the challenge for the future is to improve the accuracy of diagnosis, prognosis, and prediction of therapeutic responses through the identification of biomarkers. In this framework, the omics sciences (genomics, transcriptomics, proteomics, and metabolomics) and their combined use represent innovative approaches for the exploration of the complexity and heterogeneity of multiple sclerosis (MS). This review examines the evidence currently available on the application of omics sciences to MS, analyses the methods, their limitations, the samples used, and their characteristics, with a particular focus on biomarkers associated with the disease state, exposure to disease-modifying treatments (DMTs), and drug efficacies and safety profiles.